Factors associated with the severity of positive and negative symptoms in inpatients with schizophrenia in Vietnam: A Cross-sectional Study - Le, Tran Tuan Anh; Tran, Nhu Minh Hang; Ho, Dung; Tran, Thi Tra My; Nguyen, Thi Mai Hien (Tạp chí Y Dược Huế, 2026)
Background: Schizophrenia is a complex, debilitating disorder imposing a substantial global burden. Its symptomatic heterogeneity has prompted a shift from traditional subtypes towards a dimensional understanding, validating the positive-negative dichotomy as two core domains with divergent neurobiological substrates. While this structure is established, the specific clinical, functional, and sociodemographic factors modulating each domain’s severity can vary across populations. In Vietnam, despite schizophrenia being a significant public health concern, a critical gap exists. There is a lack of comprehensive investigations concurrently examining a broad range of associated factors for both symptom domains in an inpatient setting. Objectives: To identify factors independently associated with the severity of positive and negative symptoms among inpatients with schizophrenia in Vietnam. Materials and methods: A cross-sectional study was conducted with 121 inpatients (ICD-10 diagnosis) at Hue Psychiatric Hospital from September 2024 to April 2025. Data were collected on sociodemographic, clinical, and functional characteristics. Symptom severity was assessed using the Positive and Negative Syndrome Scale (PANSS). Cognitive and social functioning were measured with the Mini-Mental State Examination (MMSE) and Social Functioning Questionnaire (SFQ), respectively. Two separate multiple linear regression models were constructed to identify independent associated factors for PANSS positive and negative subscale scores. Results: The model for positive symptoms demonstrated a modest fit (Adjusted R² = .126, p < 0.001), identifying general polypharmacy (≥ 3 medications) as the sole independent factor associated with higher severity. The model for negative symptoms demonstrated a substantial fit (Adjusted R² = .392, p < 0.001), where higher severity was independently associated with lower cognitive (MMSE) scores, poorer social functioning, and the absence of substance use history. Conclusion: The determinants of positive and negative symptoms in schizophrenia are markedly distinct. Positive symptoms were primarily associated with clinical-diagnostic features and treatment complexity, while negative symptoms were strongly linked to cognitive and functional impairments. These findings highlight the need for personalized, dimension-specific therapeutic strategies to improve patient outcomes in Vietnam.